The Dietary Effects on Manure Characteristics and Biogas Production from Dairy Cows Feeding with Pineapple Peel - Chainetr, Siraprapa; Khiewwijit, Rungnapha; Ngoenkhumkhong, Khanchit; Chainetr, Worawut (RMUTP Research Journal Sciences and Technology, 2022)
This study explored the dietary effect on manure characteristics and potential of biogas production from the manure of dairy cows feeding with pineapple peel as a roughage source. Three mid-lactation primiparous crossbred Holstein dairy cows, which had an average body weight of 443.5±10.6 kg and average milk production of 9.6±0.3 kg/d were assigned with three different diet types including T1, T2 and T3. T1 was a control diet, which consisted of a mixture of dry Pangola grass and commercial pellet (CL). Moreover, T2 was a mixture of dry Pangola grass, pineapple peel and CL, while T3 was a mixture of pineapple peel and CL. Dairy cow manure was collected on the day 10th after feeding and anaerobic digestion of the dairy cow manure was operated with an HRT of 30 days. Results showed that all diet types gave similar manure characteristics of high organic matter and nitrogen. Average concentrations of TS and COD ranged from 82.59 to 85.78 g/L and 85.47 to 91.47 g/L, respectively, whereas TAN ranged from 1.54 to 1.67 g/L. However, a higher pH of 7.50 was found for the manure of dairy cow fed with T1, while a lower pH of 6.50 was obtained with T3. Besides, the highest methane yield of 0.20 m3 CH4/kg VSadded was obtained when using the manure of dairy cow fed with T1 as a substrate, followed by T2 and T3 which found at 0.14 and 0.11 m3 CH4/kg VSadded, respectively. This indicated the efficient potential of biogas production from the manure of dairy cows fed with pineapple peel, which will improve sustainable utilization of agricultural wastes and waste produced from dairy cow farm in the future.